2020
DOI: 10.1002/ijfe.2044
|View full text |Cite
|
Sign up to set email alerts
|

Money laundering and bank risk: Evidence from U.S. banks

Abstract: We test for a link between money laundering and bank risk in US banks. We find that money laundering increases bank risk according to several measures of risk, with the effect on risk only partly mitigated by large and independent executive boards and accentuated by powerful CEOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Altunbas et al. (2020) tested for a relationship between bank risk and the enforcements issued by US regulators against banks for money laundering (ML). ML‐related enforcements are associated with increased bank risk on several measures of risk with the result being robust to a variety of estimation methodologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altunbas et al. (2020) tested for a relationship between bank risk and the enforcements issued by US regulators against banks for money laundering (ML). ML‐related enforcements are associated with increased bank risk on several measures of risk with the result being robust to a variety of estimation methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies (Köster & Pelster, 2018) have associated the implementation of measures by regulators against misconduct in the banking industry with the level of risk taken on by these entities and have concluded that there is an increase in systemic risk. Altunbas et al (2020) tested for a relationship between bank risk and the enforcements issued by US regulators against banks for money laundering (ML). MLrelated enforcements are associated with increased It is also worth noting another group of studies that researched the effect of disciplinary sanctions on the traditional activity of banks-that is, on deposits and loans-that have significant macroeconomic effects.…”
Section: Clustersmentioning
confidence: 99%
“…In the previous literature, several studies examining the effects of ML on the financial performance of firm performance and economic development (Altunbaş et al, 2021;Shah et al (2022) determined How money laundering (ML) affects the loan portfolio quality of Islamic bank. The methodology used the data of conventional and Islamic banks of Pakistan from 2012 to 2018.…”
Section: Money Laundering and Firm Performancementioning
confidence: 99%
“…Although banking firms appear to have lower direct ES impacts relative to their industrial counterparts, banks facilitate industrial activities by lending to firms that may engage in socially irresponsible corporate behaviours such as pollution, manufacturing of hazardous products and human rights violations (Kotchen and Moon, 2012; Thompson and Cowton, 2004). Anecdotal evidence suggests that banks have been accused of facilitating unethical social behaviours such as corruption, bribery and money laundering, in addition to other dubious lending, investment and asset management practices (Altunbaş, Thornton and Uymaz, 2021; Arnold, 2018).…”
Section: Introductionmentioning
confidence: 99%